Nucleotide sequence of microvariant RNA: another small replicating molecule. - Mills, D R (1975)
Microvariant RNA, a small self-replicating molecule (114 nucleotides long), has been isolated from Qbeta replicase reactions incubated in the absence of exogenous template. Its complete nucleotide sequence has been determined. Comparison with MDV-1 RNA, a somewhat larger endogenous Qbeta replicase product (220 nucleotides long) that had previously been characterized, revealed no significant sequence similarity. Since Qbeta replicase can mediate the synthesis of both of these disparate RNA molecules, primary sequence cannot be the sole determining factor in the processes of enzyme recognition and replication. This implies that the key is to be found in the secondary or tertiary structures. The availability of two different replicating molecules of defined sequence should aid in identifying these critical structural features.